Komunitas Makrozoobentos sebagai Indikator Biologis Kualitas Air Sungai Masang Kecil yang Menerima Limbah Cair Industri Minyak Kelapa Sawit di Kinali Pasaman Barat - Izmiarti Izmiarti; Vivi Savitri (Universitas Andalas, 2018)
The industrial liquid waste of crude palm oil contains organic material that can lead to degradation of water quality and ultimately affect the macrozoobenthos communities living on the river bed. The Masang Kecil River in Kinali Pasaman Barat receives the liquid waste of the palm oil industry. The research aimed to find out the composition and structure of macrozoobentos community in Masang Kecil River and determine the water quality of river based on macrozoobenthic community structure was done in June 2017. The research was conducted by survey method with purposive sampling technique. Samples were collected on 3 stations: Station I before entering the liquid waste of palm oil industry, Station II after entering the waste, Station III is located after Station II which has been entered by Anak Aia stream. In each station collected three samples of macrozoobentos with a surber net size of 30x30 cm2. The results showed that macrozoobenthos community found 43 species consist of 33 species of Insecta, Oligochaeta 4 species, Gastropoda 3 species, Hirudinae 2 species, Arachnida and Turbellaria one species respectively. The largest number of individuals was shown by Insecta (71.89%) followed by Hirudinea (25.1%) and the other class was not more than 3%. The highest density is found at station III and the lowest at station I. The dominant species on station I were Stenelmis sp. and Psephenoides sp., stations II and III were Erphobdella sp. and Hydropsyche elisoma. The diversity index ranges from 1.49 to 3.01. The index of equitability ranges from 0.47 to 0.89, the dominant index ranges from 0.06 to 0.43. The similarity of communities between station ranged from 38.46 - 55.0%. Based on the index of diversity, water quality in Station I was classified as not polluted, Station II and III classified as moderate.